Síntese e avaliação da atividade biológica de derivados hexaidroquinolínicos - Moreira, Monalisa Azevedo (2020)
A multicomponent, or multicomponent (RMC) mixture, is used to use three or more elements to obtain a final product with all, or a major part of, the carbon atoms contained in the starting material. These restrictions require little laboratory manipulation, can be done without use or increased temperature, and can be used for products with complex carbonic structure and, therefore, are useful for the chemistry of bioactive compounds. Like RMC, they were explored between 1850 and 1882 and, after that period, a smaller amount of studies was caused by lack of economic interest. Currently, these changes are again the focus of many researches, mainly because they comply with the principles of green chemistry. The nitrogenous heterocyclic compounds, for example, arouse a special interest because they present a wide spectrum of applications within chemistry, with emphasis on the chemistry of natural products. The interest in the exposure of hexahydroquinolines is great due to its wide biological potential. In view of the above, the objective of this project was synthesized, through the RMC, six hexahydroquinoline, as well as their characteristics applicable to NMR and IV, and evaluates the activity of these derivatives against Escherichia Coli (Gran Negative), Staphylococcus Aureus ( Gran positive) and Aspergillus Ochraceus fungus. As substances, a mixture of different aromatic aldehydes (2 mmol), 1,3-cyclohexanedione (2 mmol) or 5,5dimethylcyclohex-1,3-cyclohexanedione, ethyl acetoacetate (2 mmol) and ethyl acetate ammonium was removed. (3 mmol), obtaining 6 (six) hexahydroquinoline derivatives. A methodology consists in the maceration of 4 substances in a mortar, obtaining a final crystallized product. A structural characterization was made by 1H and 13C NMR (600 MHz), and vibrational spectroscopy in the Infrared (IV) region, with Fourrier transform. NMR is a technique with greater power to determine an organic structure. The results shown as six substances were selected successfully, with yields varying between 26% and 79%. As NMR and IV spectroscopies, they elucidated in detail how structures and confirmed the identity of all expected products for a multicomponent of hexahydroquinolines. The testicles against E. Coli, S. Aureus, and for the fungus A. Ochraceus, with a maximum of 500 μg / ml, without biological activity.